AN ANALYSIS OF HYPERBOLE USED IN HEART OF DARKNESS BY JOSEPH CONRAD - Rafi Haryadi; Yusmalinda Yusmalinda (STBA Prayoga Padang, 2022)
Abstract The purpose of this research was to identify the forms of hyperbole found in Heart of Darkness by Joseph Conrad. The research data were taken from the novel Heart of Darkness by Joseph Conrad. The writer applied Claridge’s theory to classify the forms of hyperbole. There are seven forms of hyperbole. They are single-word hyperbole, phrasal hyperbole, clausal hyperbole, numerical hyperbole, hyperbolic superlatives, hyperbolic comparison, and hyperbolic repetition. This study was qualitative research. This study reveals that seven forms of hyperbole according to Claridge (2011) were found in Heart of Darkness by Joseph Conrad. The forms are single-word hyperbole, phrasal hyperbole, clausal hyperbole, numerical hyperbole, the role of the superlative, comparison, and repetition. From the occurrence of all seven forms of hyperbole, it was found that the most form of hyperbole was clausalhyperbole. In conclusion, it can be said that Joseph Conrad used all forms of hyperbole in the novel Heart of Darkness.